Localization and biochemical characterization of the ORF6 gene product of the Mycoplasma pneumoniae P1 operon. - Layh-Schmitt, G (1992)
ORF6 represents one of the two open reading frames flanking the P1 attachment protein gene of Mycoplasma pneumoniae in the order ORF4-P1-ORF6 (J.M. Inamine, T.P. Denny, S. Loechel, U. Schaper, C.H. Huang, K.F. Bott, and P.C. Hu, Gene 64:217-219, 1988; J.M. Inamine, S. Loechel, and P.C. Hu, Gene 73:175-183, 1988; C.J. Su, V.V. Tryon, and J.B. Baseman, Infect. Immun. 55:3023-3029, 1987), indicating an operonlike organization. As described previously, we identified two proteins with molecular masses of 40 and 90 kDa (B. Sperker, P.C. Hu, and R. Herrmann, Mol. Microbiol. 5:299-306, 1991) which might represent two cotranslational cleavage fragments of the ORF6 gene product. To determine the site of the putative cotranslational cleavage, the first 10 amino acids of the N terminus of the isolated 90-kDa protein were sequenced. The data are consistent with the DNA-deduced amino acid sequence between amino acid positions 455 and 465 (RAGNSSETDAL). Thus, the cleavage site was identified at amino acid position 455 (R). In this study, the two proteins were localized and biochemically characterized. Both proteins are part of the insoluble fraction of M. pneumoniae as shown by immunoblots of supernatants and pellets of mechanically disrupted cells subjected to sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE). Surface proteolysis followed by SDS-PAGE and Western blot (immunoblot) analysis, covalent labelling of surface-exposed proteins with [125I]iodide and subsequent immunoprecipitation of both radiolabelled proteins, immunofluorescence studies with formalized and living M. pneumoniae, and immunoadsorption experiments provided strong evidence that the 40- and 90-kDa proteins are membrane-associated proteins expressing surface-exposed regions.